Brincando de amarelinha: a produção do Parque Nacional Tierra Del Fuego - Brenda Ponzi (Confins)
Territoriality is considered the political project of an agent, which is carried out through a process called territorialization. The implementation of this territoriality, through normative and material processes, results in the production of a territory. Considering this, the Tierra del Fuego National Park is a state protected area managed by the Administración de Parques Nacionales (APN) and disputed by multiple territorialities. With regards to the territorialization process, four areas of tension between agents were analyzed in order to understand the way that they challenge the decisive power of the APN. The analysis included a bibliographic review and semi-structured interviews that were conducted with key informants related to the construction of the protected area. In conclusion, the jurisdictional and competence conflicts between different organizations, as well as the projects of private agents, make the construction of the national protected area more complex; therefore, challenging the material and normative mission of APN.